Upward Intercultural Communication in Multinational Company: What Matters the Most - Annie Susanto; Yunita Budi Rahayu Silintowe; Rosaly Franksiska; Johnson Dongoran (Universitas Pendidikan Ganesha, 2023)
Effective communication is necessary at work, especially when it involves different cultures. To avoid cultural conflicts, parties involved in communication should realize the barriers hindering the communication process. This research explored and mapped the upward intercultural communication barriers within multinational companies in Indonesia and the factors contributing to those barriers. This qualitative research involves 16 employees from nine multinational companies as informants. In this research, the superiors and the subordinates are from different cultural backgrounds. The informants of this study were selected through a snowball approach, starting at several companies in an industrial area in Central Java. The informants were contacted and given several questions such as age, length of employment, and superior’s characteristics as a control variable. The next step was an interview of informants using open-ended interview guides. For triangulation, after all the interviews, FGDs were held two times, and last, for confirmation, the informants were asked to comment on or revise the data. The general barriers found in this research were semantics (in terms of language), physical (in terms of physical distance), and contextual (in terms of working system disapproval). The factors contributing to those barriers are stereotypes, perceptions, and educational backgrounds and experiences.